Plasma Gasification of Biomedical Waste: Energetic and Exergetic Aspect - Paulino, R. Franciélle Silva [UNESP]; Silveira, J. Luz [UNESP] (Springer Nature, 2024)
Plasma gasification technology can process solid municipal, commercial, industrial, petrochemical, and healthcare waste and produce ash and syngas that can be used to generate thermal and/or electrical energy. This is still a little-known technology because it has a high consumption of electricity and a high economic cost, but it can be an alternative for the processing of solid waste from biomedical waste (BW) due to the need for stricter disposal processes. Considering that Brazil and the world have serious problems with the incorrect disposal of biomedical waste (BW) and the increase in the generation of this type of waste due to the COVID-19 pandemic, it is necessary to expand the studies of plasma gasification technology for processing and disposal of the BW of Brazilian cities and cities in every country in the world. In this context, this book chapter aims to carry out energy studies to determine the potential for electric power generation in an internal combustion engine (ICE) and a gas turbine set (GTS), operating with syngas gas produced by the gasification system to plasma and to allocate this electricity to the plasma gasifier and determined out the percentage that both the internal combustion engine and the gas turbine assembly can meet the need for the plasma gasification process. And also carry out exergetic studies to determine the efficiency of Second Law and Bonokovic, and even the irreversibilities of each piece of equipment of the proposed systems to evaluate where the greatest losses are. As a conclusion of the energy studies, the plasma gasification process is promising when associated with an internal combustion engine or gas turbine set, producing 2772.54 and 3741.63 kW of electricity, respectively, and also the internal combustion engine and the gas turbine set can supply 37% and 51%, respectively, of the electrical energy required in the plasma gasification process. Through the exergetic analysis, the plasma gasifier proved to be the most irreversible equipment (21,430 kW) both associated with the internal combustion engine and gas turbine set. Therefore, it is the plasma gasifier that studies should focus on developing more efficient equipment and making the plasma gasification process more attractive.
Keywords: Biomedical waste; Energetic analysis; Exergetic analysis; Plasma gasification; Syngas